2016
DOI: 10.1590/0004-282x20160101
|View full text |Cite
|
Sign up to set email alerts
|

Are astrocytes executive cells within the central nervous system?

Abstract: Experimental evidence suggests that astrocytes play a crucial role in the physiology of the central nervous system (CNS) by modulating synaptic activity and plasticity. Based on what is currently known we postulate that astrocytes are fundamental, along with neurons, for the information processing that takes place within the CNS. On the other hand, experimental findings and human observations signal that some of the primary degenerative diseases of the CNS, like frontotemporal dementia, Parkinson’s disease, Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…It has been reported that reactive astrocytes are harmful for axonal regeneration and remyelination. 56,57 Previous studies have demonstrated that astrocyte ablation can improve the remyelination in the demyelination mouse model. 58 The present study has similar findings, in which the density of GFAP + cells significantly decreased at day 35 with KD administration.…”
Section: ■ Discussionsupporting
confidence: 89%
“…It has been reported that reactive astrocytes are harmful for axonal regeneration and remyelination. 56,57 Previous studies have demonstrated that astrocyte ablation can improve the remyelination in the demyelination mouse model. 58 The present study has similar findings, in which the density of GFAP + cells significantly decreased at day 35 with KD administration.…”
Section: ■ Discussionsupporting
confidence: 89%
“…Further studies in disease modelling of FTD3 using iPSCs will potentially reveal additional novel disease phenotypes and therapeutic strategies. The central nervous system holds a glial/neuron ratio of 1.48 (Friede and Van Houten, 1962;Sica et al, 2016), which emphasize the glial importance and points towards potential pathological implications of glia in neurodegenerative disorders like FTD. Consequently, we applied an astrocyte differentiation protocol where growth factor supplements, mimicking in vivo embryonic astrogenesis, promoted the differentiation and maturation of the neuronal progenitor cells into astrocyte progenitors and further towards astrocytes expressing the astrocytic markers AQP4, S100β, SOX9 and GFAP (unpublished data).…”
Section: Human Ipscs For Modelling Neurodegenerationmentioning
confidence: 99%
“…In this context, astrocytes have been studied concerning their role in the pathophysiology of status epilepticus and their importance in the homeostatic balance of the central nervous system. activation causes the modulation of synaptic activity and neuroplasticity (5). Therefore, significant astrocytic damage contributes to epileptic seizures associated with intense neuronal firing, especially when seizures occur around the nucleus of the lesion (6).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes respond to all forms of aggression in the central nervous system (CNS) through a process called reactive astrogliosis, a pathognomonic sign of structural damage to this organ ( 3 , 4 ). Concomitantly, astrocytic activation causes the modulation of synaptic activity and neuroplasticity ( 5 ). Therefore, significant astrocytic damage contributes to epileptic seizures associated with intense neuronal firing, especially when seizures occur around the nucleus of the lesion ( 6 ).…”
Section: Introductionmentioning
confidence: 99%